AgNO3-catalyzed direct C–H arylation of quinolines by oxidative decarboxylation of aromatic carboxylic acids. Issue 4 (19th January 2017) - Yuan, Jin-Wei; Yang, Liang-Ru; Mao, Pu; Qu, Ling-Bo
Abstract : AgNO3 -catalyzed direct C–H arylation of quinolines by oxidative decarboxylation of aromatic carboxylic acids to afford aryl quinoline derivatives in moderate yields was described. Abstract : An efficient silver-catalyzed intermolecular decarboxylative arylation of quinolines has been developed using cheap aromatic carboxylic acids as arylating reagents under microwave irradiation. The reaction demonstrates a broad substrate scope and excellent functional group tolerance. This method provided an effective and easy way to synthesize arylated quinoline derivatives. The radical trapping experiments showed that this process involved the radical mechanism.